Evaluation of MOS social support in low-income caregivers of African American children with poorly controlled asthma. (2nd September 2019) - Margolis, Rachel; Bellin, Melissa H.; Sacco, Paul; Harrington, Donna; Butz, Arlene
Abstract: Objective: The purpose of this study was to examine the factor structure of the Medical Outcomes Study Social Support Survey (MOS-SSS) in a sample of low-income, urban caregivers of African American children with poorly controlled asthma. Although the MOS-SSS is a commonly used measure of social support, its psychometric properties have not been studied in this population. Methods: Confirmatory factor analysis was conducted to determine the most appropriate factor structure for the MOS-SSS in caregivers of African American children with frequent Emergency Department visits for uncontrolled asthma. The following models were tested and compared using established fit statistics: an 18-item second-order four factor model, an 18-item four factor model, a bifactor model and an 18-item one factor model with nested models. Results: Participating caregivers were single (75.6%) and female (97%). An 18-item one factor version of the scale had the best fit statistics compared to the other models tested: χ 2 (142) = 308.319, p > 0.001; Root mean square error of approximation (RMSEA) = 0.077; CFI (Comparative Fit Index) = 0.990; and Tucker-Lewis Index (TLI) = 0.988. Construct validity was supported by a statistically significant negative relationship between our final MOS-SSS model and caregiver depressive symptoms ( β = −0.374, p < 0.001). Conclusions: The 18-item one factor MOS-SSS may be appropriate for use in research and clinical practice with caregivers of African American children with poorly controlled asthma. It appears promising as a mechanism to advance understanding of relationships between social support and asthma outcomes in this vulnerable population.